The mechanics of inhaled pharmaceutical aerosols an introduction - Finlay, Warren H. (Academic Press, 2001)
The Mechanics of Inhaled Pharmaceutical Aerosols, An Introduction provides a unique and comprehensive treatment of the mechanics of inhaled pharmaceutical aerosols. The book covers a wide range of topics and many new perspectives are given by drawing on research from a variety of fields. Novel, in-depth expositions of the most common delivery devices are given, including nebulizers, dry powder inhalers and propellant metered dose inhalers. The behaviour of aerosols in the respiratory tract is explained in detail, with complete coverage of the fundamentals of current deposition models. The book begins by providing a comprehensive introduction to aspects of aerosol mechanics that are relevant to inhaled pharmaceutical aerosols. It then gives an exhaustive pedagogical description of the behaviour of evaporating and condensing droplets (both aqueous and propellant-based), an introductory chapter on lung geometry and inhalation patterns, and coverage of relevant aspects of fluid mechanics in the lung. Finally, the book provides invaluable, detailed coverage on the mechanics of common pharmaceutical aerosol delivery systems and deposition in the respiratory tract. Throughout the book are many detailed numerical examples that apply the salient concepts to typical inhaled pharmaceutical aerosols. This book will be of interest to scientists and engineers involved in the research and development of inhaled pharmaceutical aerosol products. Experienced practitioners will find many new perspectives that will greatly enhance their understanding of this complex and rapidly growing field. For those delivering therapeutic agents to the lung, this book is a must-have. Students and academics will find this book an invaluable tool and for newcomers it is a worthy guide to the diverse fields that must be understood to work in the area of inhaled pharmaceutical aerosols.